Preparation and Characterization of Extruded Composites Based on Polypropylene and Chitosan Compatibilized with Polypropylene-Graft-Maleic Anhydride - Carrasco-Guigón, Fernando Javier (Materials (Basel), 2017)
The preparation of composites of synthetic and natural polymers represent an interesting option to combine properties; in this manner, polypropylene and chitosan extruded films using a different proportion of components and polypropylene-graft-maleic anhydride (PPgMA) as compatibilizer were prepared. The effect of the content of the biopolymer in the polypropylene (PP) matrix, the addition of compatibilizer, and the particle size on the properties of the composites was analyzed using characterization by fourier transform-infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), differential scanning calorimetry (DSC), tensile strength, and contact angle, finding that in general, the addition of the compatibilizer and reducing the particle size of the chitosan, favored the physicochemical and morphological properties of the films.